Detection of BMAA in the human central nervous system. (30th April 2015) - Berntzon, L.; Ronnevi, L.O.; Bergman, B.; Eriksson, J.
Highlights: The phytoplanktonic neurotoxin BMAA detected in human central nervous system. 12 ALS patients and 13 controls examined for BMAA with UHPLC–MS/MS. BMAA found in cerebrospinal fluid of 1 ALS patient and 2 controls. BMAA was not prevalent in ALS patients. Abstract: Amyotrophic lateral sclerosis (ALS) is an extremely devastating neurodegenerative disease with an obscure etiology. The amino acid β- N -methyl-l -alanine (BMAA) produced by globally widespread phytoplankton has been implicated in the etiology of human motor neuron diseases. BMAA was recently proven to be present in Baltic Sea food webs, ranging from plankton to larger Baltic Sea organisms, some serving as important food items (fish) for humans. To test whether exposure to BMAA in a Baltic Sea setting is reflected in humans, blood and cerebrospinal fluid (CSF) from individuals suffering from ALS were analyzed, together with sex- and age-matched individuals not inflicted with ALS. Ultra high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) and multiple reaction monitoring (MRM), in conjunction with diagnostic transitions revealed BMAA in three (12%) of the totally 25 Swedish individuals tested, with no preference for those suffering from ALS. The three BMAA-positive samples were all retrieved from the CSF, while BMAA was not detected in the blood. The data show that BMAA, potentially originating from Baltic Sea phytoplankton, may reach the human central nervous system, but does not lend support to the notion that BMAA is resident specifically in ALS-patients. However, while dietary exposure to BMAA may be intermittent and, if so, difficult to detect, our data provide the first demonstration of BMAA in the central nervous system of human individuals ante mortem quantified with UHPLC–MS/MS, and therefore calls for extended research efforts.